2018
DOI: 10.7717/peerj.4795
|View full text |Cite
|
Sign up to set email alerts
|

A guideline for reporting experimental protocols in life sciences

Abstract: Experimental protocols are key when planning, performing and publishing research in many disciplines, especially in relation to the reporting of materials and methods. However, they vary in their content, structure and associated data elements. This article presents a guideline for describing key content for reporting experimental protocols in the domain of life sciences, together with the methodology followed in order to develop such guideline. As part of our work, we propose a checklist that contains 17 data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…We have analyzed: i) guidelines for authors from journals publishing protocols (Giraldo et al, 2018b), ii) our corpus of protocols (Giraldo et al, 2018a), iii) a set of reporting structures proposed by minimal information projects available in the FairSharing catalog (McQuilton et al, 2016) and, iv) relevant biomedical ontologies available in BioPortal (Whetzel et al, 2011) and Ontobee (Xiang et al, 2011). Our analysis was carried out by a domain expert, Olga Giraldo; she is an expert in text mining and biomedical ontologies with over ten years of experience in laboratory techniques.…”
Section: Methodsmentioning
confidence: 99%
“…We have analyzed: i) guidelines for authors from journals publishing protocols (Giraldo et al, 2018b), ii) our corpus of protocols (Giraldo et al, 2018a), iii) a set of reporting structures proposed by minimal information projects available in the FairSharing catalog (McQuilton et al, 2016) and, iv) relevant biomedical ontologies available in BioPortal (Whetzel et al, 2011) and Ontobee (Xiang et al, 2011). Our analysis was carried out by a domain expert, Olga Giraldo; she is an expert in text mining and biomedical ontologies with over ten years of experience in laboratory techniques.…”
Section: Methodsmentioning
confidence: 99%
“…These exercises are designed to eventually be selfguided in the stroke survivors' home and facilitate continued progress. According to Giraldo et al, 2018. different variations in the experimental protocol are possible by using the setup of mirror therapy. Moreover, in the study conducted by Thieme (2012), the intervention is extended with a combination of mirror therapy and other therapies in the experimental condition, in which a minimum of 50% from the experimental intervention time was applied as for mirror therapy.…”
Section: Clinical Procedures and Post-medical Treatmentmentioning
confidence: 99%
“…The risk of variation in RT, similar to the absence of clearly defining the commercial sources of chemical reagents or other laboratory equipment [20], is that it may introduce errors into an experimental methodology, or result in failure or erroneous outcomes, thereby reducing the reproducibility of the findings. Given this risk, and considering that few, if any, current guidelines explicitly request this [21], it is suggested that experiments or procedures conducted at RT define the precise temperature, including if such experiments are conducted in temperature-controlled chambers.…”
Section: Possible Reproducibility Risks Of Not Defining Rt: Conclusion and Suggestionsmentioning
confidence: 99%